Feiyanning formula modulates the molecular mechanism of osimertinib resistance in lung cancer by regulating the Wnt/β-catenin pathway - Sang, Shuliu; Sun, Chenbing; Ding, Rongzhen; Jiang, Jingjie; Han, Yang; Gan, Shanshan; Bi, Ling; Gong, Yabin (Frontiers in Pharmacology, 2022)
Feiyanning Formula (FYN), a Chinese herbal formula derived from summarized clinical experience, is proven to have anti-tumor effects in lung cancer patients. Osimertinib, a third-generation epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI), can improve progression-free survival and overall survival of patients but drug resistance is inevitable. The current study evaluated the effects of FYN in osimertinib-resistant HCC827OR and PC9OR cells. FYN preferentially inhibited the proliferation and migration of HCC827OR and PC9OR cells. Moreover, FYN and osimertinib exhibited synergistic inhibitory effects on proliferation and migration. Real-time qPCR (RT-qPCR) and western blotting results indicated that FYN downregulated gene and protein levels of GSK3β and SRFS1, which are enriched in the Wnt/β-catenin pathway. Besides, FYN inhibited tumor growth and exhibited synergistic effects with osimertinib in vivo. Collectively, the results suggested that FYN exerted an anti-osimertinib resistance effect via the Wnt/β-catenin pathway.